An introduction to visual culture - Mirzoeff, Nicholas 1962- (London Routledge, an imprint of the Taylor & Francis Group, 2023)
"In the fully rewritten third edition of this classic text, Nicholas Mirzoeff introduces visual culture as visual activism, or activating the visible. In this view, visual culture is a practice: a way of doing, making and seeing. The twelve new chapters begin with five foundational concepts, including Indigenous ways of seeing, visual activism in the wake of slavery and unfixing the gaze. The second section outlines three currently successful tactics of visual activism: removal of statues and monuments; restitution of cultural property; and practices of repair and reparations. The final section addresses catastrophe and trauma, from Palestine's Nakba to the climate disaster and the intersections of plague and war. Each section also includes new, in-depth case studies called "Visualizations", ranging from oil painting to Kongo power figures and the mediated practice of taking a knee. Engaging with questions of racializing, colonialism and undoing gender throughout, this edition maps the activist turn in the field since 2014 and sets directions for its future expansion. This is a key text in visual culture studies and an essential resource for research and teaching in the field"-- Provided by publisher.
Keywords: Art and society; Visual communication; Visual perception; Mass media; Communication and culture; Postmodernism